Waqf Management, Governance, And Accountability Practices: The State Of The Contemporary Literature - Yaacob, Hisham; Syed Yusuf, Sharifah Norzehan; Mohamed, Intan Salwani; Mohamad, Maslinawati; Nahar, Hairul Suhaimi (Journal of Islamic, Social, Economics and Development, 2025)
Waqf (plural: awqaf) is an Islamic endowment that gives the waqif (benefactor) a continuing good deed. Awqaf has proven to be effective socio-economic contributing public goods such as education, healthcare, and food since the beginning of Islam at no cost to Muslim society. This paper intends to examine extant literature on waqf management, governance and accountability in Scopus database. The result indicates three main themes of waqf management and administration, disclosures and risks management, and governance and administration dominate the waqf literature. It is therefore suggested that future research should ideally focus more on the in-depth study in waqf actual settings to better understand the issues and challenges confronting the management and governance practices that are vital to achieving greater accountability to the waqf stakeholders and ensuring waqf growth and sustainability.